THE KNOWLEDGE OF FOREST CONSERVATION ATTITUDES AND BEHAVIORS IN ELEMENTARY SCHOOL STUDENTS AROUND TWA PUNTI KAYU AREA IN PALEMBANG CITY SOUTH SUMATERA PROVINCE - Putra, Ahwansah; Helida, Asvic; Lensari, S.Hut, M.Si, Delfy (Universitas Muhammadiyah Palembang, 2023)
Environmental issues and nature conservation are very complex problems and are our responsibility together. Therefore the provision of information as early as possible to students is very good and most likely will always be remembered all the time and be embedded in the heart of their conscience. The knowledge, attitudes and good behavior of forests in the young generation will make a solid foundation to keep the forest in the future. This research aims to measure and analyze the level of knowledge, attitudes and behavior of elementary school students to the conservation of forest in the lifeboats Park Punti Kayu Palembang City, South Sumatera province. This research was implemented in 2 (two) elementary school namely SD Negeri 237 and SD Negeri 238 Palembang South Sumatera province. The selection of schools is conducted using Pruposive sampling, which is a nonrandom (non-randomized) sampling technique for non-specific populations, with specific consideration criteria which is the school distance ? 2 km from TWA Punti Kayu Kota Palembang South Sumatera Province. The research methods used are field observations, interviews with questionnaires, and library studies. Sampling technique using the formula Slovin with the number of respondents as many as 40 students. The data collection done is to provide 10 question items in the knowledge variable, 10 question items in attitude variables and 10 question items in behavior variables. The results show that (1) the level of knowledge, students ' attitudes and behaviors on forest conservation are in good category. (2) Factors that influence is the use of learning media in the process of learning teaching and application of forest conservation education on environmental education material, in this case both have each other a correlation so that it affects the level of Knowledge, attitudes and behaviors.